Policy Reforms Positioning Preschool Teachers from Invisible to Visible - Öqvist, Anna; Cervantes, Sara (International Journal of Education Policy and Leadership, 2025)
Since 1972, Swedish preschool has undergone several policy reforms. Since 2010, preschool teachers have been given increased responsibility for education and its pedagogical content, which preschool teachers have identified as challenging. This study analyzes how policies have positioned preschool teachers and how these policies impact their responsibilities. Drawing on positioning theory and a qualitative analysis of seven policy documents, the study shows that preschool teachers were invisible between 1972 and 2010, gaining visibility after 2010. The findings reveal that policies can both marginalize and reinforce their role. Policy is a key lever for redefining responsibilities and redistributing power. Clarifying shared responsibilities with the educational team is crucial to avoid ambiguity.